Absence of deficits in social behaviors and ultrasonic vocalizations in later generations of mice lacking neuroligin4 - Ey, E. (Genes Brain Behav, 2012)
Mutations in NLGN4X have been identified in individuals with autism spectrum disorders and other neurodevelopmental disorders. A previous study reported that adult male mice lacking neuroligin4 (Nlgn4) displayed social approach deficits in the three-chambered test, altered aggressive behaviors and reduced ultrasonic vocalizations. To replicate and extend these findings, independent comprehensive analyses of autism-relevant behavioral phenotypes were conducted in later generations of the same line of Nlgn4 mutant mice at the National Institute of Mental Health in Bethesda, MD, USA and at the Institut Pasteur in Paris, France. Adult social approach was normal in all three genotypes of Nlgn4 mice tested at both sites. Reciprocal social interactions in juveniles were similarly normal across genotypes. No genotype differences were detected in ultrasonic vocalizations in pups separated from the nest or in adults during reciprocal social interactions. Anxiety-like behaviors, self-grooming, rotarod and open field exploration did not differ across genotypes, and measures of developmental milestones and general health were normal. Our findings indicate an absence of autism-relevant behavioral phenotypes in subsequent generations of Nlgn4 mice tested at two locations. Testing environment and methods differed from the original study in some aspects, although the presence of normal sociability was seen in all genotypes when methods taken from Jamain et al. (2008) were used. The divergent results obtained from this study indicate that phenotypes may not be replicable across breeding generations, and highlight the significant roles of environmental, generational and/or procedural factors on behavioral phenotypes.